IMPROVEMENT OF EDUCATIONAL QUALITY MANAGEMENT PROCESSES IN THE MARKET OF EDUCATIONAL SERVICES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article the ways of introducing innovations in educational organizations, the results and effects of the use of innovative technologies in educational management were considered in the article. Using the example of the structural and functional model of innovative processes in modern education, an offer was made to consider the classification of innovative activities, and an analysis was given based on the table